Problems of development of China’s banking system. (Journal of Economic Research & Business Administration, 2016)
An important role in countrys socio-economic development and financial resources efficient allocation in China today is assigned to banks. In order to determine the national features of the banking system the paper presents a retrospective analysis of problems of banking systems in China. It is shown that a dominant position on the market is shared by «big four» banks controlled by the Chinese government. The current problems of banking regulation in China, related to emergence of alternative financial intermediation agents and development of new markets for banking products and services, are identified. It is concluded that deepening banking reform in China, the transformation of banks into real modern banks. Building market economic system – a complex and lengthy process. It is impossible to solve all problems at once, but that does not mean that the banking reform should move slowly. Experience in other countries shows that the time allotted for the reform of the banking system is limited.
Keywords: Chinese banking system; the development of Chinese banking system; problems of development of the banking system; central bank; commercial banks.